PEMANFAATAN MICROSOFT WORD DALAM MENINGKATKAN KETERAMPILAN PENGOLAHAN DOKUMEN SISWI SMP IBRAHIMY 3 SUKOREJO - Zaehol Fatah; Ardila Dwi Putri (CV. Denasya Smart Publisher, 2026)
The ability to operate Microsoft Word to manage documents is an essential component of digital literacy that students must possess to support academic activities. However, a number of female students at Ibrahimy 3 Junior High School, Sukorejo, still face obstacles when applying basic word processing functions, including page configuration, text arrangement, heading utilization, automatic table of contents creation, and table creation. The Microsoft Word training attended by 30 eighth-grade female students of Ibrahimy 3 Junior High School, Sukorejo, aimed to improve students' document processing skills. This community service activity used a qualitative descriptive method divided into three stages: preparation, implementation, and evaluation. The main focus of the research was to describe the process and achievements of the training. The training integrated three main methods: lectures, live demonstrations, and guided practice. The material presented included margin settings, font and paragraph formatting, heading creation, automatic table of contents, page numbering, and table insertion. The participants' ability to produce neat documents significantly improved after participating in this activity. Previously, participants were only able to type plain text, but now the students are able to compose well-structured and formatted documents. Practical and guided training has proven effective in strengthening the digital document processing skills of junior high school students based on this activity.